Neonatal Intensive Care Units Nurses’ Attitude Toward Advantages and Disadvantages of Open vs Closed Endotracheal Suction - Valizadeh, Leila (Nurs Midwifery Stud, 2014)
BACKGROUND: The vital issue of protecting the airway and maintaining ventilation in preterm infants makes tracheal suctioning an important procedure. The decision to use closed or open endotracheal suction method depends on the clinical status of infants and the nurses’ skills and preferences. OBJECTIVES: The current study aimed to compare the two methods based on the perceptions of the nurses working in Neonatal Intensive Care Units (NICU). PATIENTS AND METHODS: A comparative-descriptive study carried out on 35 NICU nurses in Taleghani and Al-Zahra teaching hospitals in Tabriz, Iran, in 2013. Data were collected by self-administered questionnaire (13 Items). Data analysis, including t-test was performed using SPSS Ver. 13. A P ≤ 0.05 was considered statistically significant. RESULTS: According to the nurses’ point of view, there are differences between characteristics of open and closed endotracheal suctioning methods (P < 0.001). By using closed endotracheal suction, the risk of traumatizing airway, developing pneumonia, increasing intracranial pressure, prolonging emergency suctioning, developing intra-ventricular hemorrhage, blood stream infection, physiological instability and lowering positive end-expiratory pressure (PEEP) are reduced. Meanwhile, lower cost, lower risk of extubation, comfort and easy washing procedure were reported as advantages of open suction. CONCLUSION: Closed endotracheal suctioning was evaluated to be better than the open method in the preterm neonates. More studies, especially experimental and efficient cost analysis, are recommended.